(untitled) - Hayes, Robert H. (New York, 1984)
This problem solver offers a wealth of remedies for American industry's neglect of competitive manufacturing strategies and its resulting loss of productivity. Drawing upon the example of world-class and foreign manufacturers, the book illustrates what American industry must do in terms of manufacturing capability to regain a preeminent spot in the marketplace.
Keywords: Manufacturing industries,Industrial management,Production planning.,Manufacturing processes; Management,Technological innovations; United states,United states